From extended feature models to constraint logic programming - Karataş, Ahmet Serkan; Oğuztüzün, Halit; Doğru, Ali (Science of computer programming, 2013)
Since feature models for realistic product families may be quite complicated, the automated analysis of feature models is desirable. Although several approaches reported in the literature address this issue, complex cross-tree relationships involving attributes in extended feature models have not been handled. In this article, we introduce a mapping from extended feature models to constraint logic programming over finite domains. This mapping is used to translate into constraint logic programs; basic, cardinality-based and extended feature models, which can include complex cross-tree relationships involving attributes. This translation enables the use of off-the-shelf constraint solvers for the automated analysis of extended feature models involving such complex relationships. We also present the performance results of some well-known analysis operations on an example translated model. ► We precisely define the syntax for the relationships in extended feature models. ► We present a mapping from extended feature models to CLP(FD). ► This mapping can handle complex cross-tree relationships involving attributes. ► This mapping also handles cardinality-based feature models. ► We present experimental performance results of some essential analysis operations.